The employment of a theatre-based workshop to support professional identity formation for medical students in a palliative medicine clerkship: an exploratory qualitative study - Eng Koon Ong; Min Chiam; April Thant Aung; Janelle Chan; Lalit Kumar Radha Krishna; Yingxuan Chen; Filomar Cortezano Tariao; Faith Ng; Jamie Zhou; Wen-Shan Sim (BMC Medical Education, 2026)
Abstract Background While theatre-based pedagogical approaches have been widely adopted in medical education globally, the medium’s potential to support professional identity formation (PIF), a crucial component of medical education, has received little attention. Through embodied representations of illness experience, suffering, death, medicine, challenges, loss, burnout, and interpersonal relationships, theatre can serve as a powerful catalyst for reflection on professional identity formation (PIF). At the same time, existing arts- and humanities-based approaches to support PIF remain situated in pre-clinical settings, with limited attention to their role within clinical clerkships. This study explored how a theatre-based humanities workshop embedded within a palliative care clerkship shaped the professional identity of medical students. Methods This prospective exploratory qualitative study involved final-year medical students who participated in a theatre-based medical humanities workshop during a palliative care clinical clerkship. The workshop centred on a professionally produced theatre play depicting a palliative care physician navigating clinical decision-making, interprofessional conflict, family caregiving responsibilities, and questions of meaning and purpose at the end of life. Individual semi-structured interviews explored students’ experiences of the workshop and its perceived influence on professional identity formation. Interviews were audio-recorded, transcribed, and anonymised. Data were analysed thematically with independent coding and iterative discussions conducted to refine themes. Results Twelve medical students participated and three interrelated themes were identified. First, students described dissonance between their expectations of professional conduct and observed clinical practices, particularly in relation to communication, interprofessional relationships, and wellbeing. Second, students attempted to make sense of this dissonance through pragmatic adjustments to practice shaped by systemic constraints, often accompanied by anxiety, self-reproach, and shame. Third, the palliative care clerkship, together with the workshop, offered alternative models of practice that emphasised relational care, recognition of the limits of medicine, and greater awareness of how personal roles and experiences influence professional identity. Conclusion This study suggests that a humanities-based workshop embedded within a palliative care clerkship can provide a meaningful space for final-year medical students to reflect on professional identity at this critical transition point. By engaging with lived experiences, contextual constraints, and role negotiation, such interventions may complement clinical training and support professional identity formation in ways that are responsive to students’ realities. Thoughtful integration of arts- and humanities-based approaches into clinical medical education may strengthen efforts to support professional identity formation across the continuum of training.